A study on how an advertising agency works & ensures client satisfaction in context of Ogilvy & Mather, Bangladesh - Morshed, Foyzul Kabir (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2013.